AT-TASYBIH WA AL-ISTI’ARAH DALAM AL-QUR’AN: PENGERTIAN, KAIDAH, DAN PENERAPANNYA - Anugrah Pangestu; Ahmad Dasuki (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This article discusses At-Tasybih and Al-Isti‘arah as important elements in the study of balaghah and Qur’anic interpretation. The study aims to explain the definitions of tasybih and isti‘arah, describe their rules and elements, and analyze their application in the verses of the Qur’an. The research focuses on three main problems, namely the meaning of At-Tasybih wa Al-Isti‘arah, the principles and forms of both styles, and their implementation in the Qur’an. This study uses a qualitative descriptive method with a literature study approach by analyzing books of tafsir, balaghah, and related scientific journals. The results show that tasybih functions as an explicit comparison between two things based on similar characteristics, while isti‘arah uses figurative expressions to convey deeper meanings. Both styles have significant roles in strengthening meaning, beautifying language, and clarifying Qur’anic messages. Examples found in several Qur’anic verses demonstrate that the use of tasybih and isti‘arah contributes to the rhetorical and aesthetic beauty of the Qur’an while also providing spiritual and moral values for readers. Therefore, understanding these rhetorical styles is essential in order to interpret Qur’anic verses comprehensively and accurately. The study concludes that At-Tasybih and Al-Isti‘arah are important aspects of Qur’anic linguistic miracles and have major relevance in the study of balaghah and tafsir.